360 Degree Feedback as a Technique of Performance Appraisal: Does it Really Work? - Hosain, Md. Sajjad (Asian Business Review, 2016)
The overall performance of a firm is mostly dependent on the individual and group performance of the organization. Performance appraisal is a continuous process of monitoring, managing and correcting the individual performance of entire workforce. 360 degree feedback is considered as one of the yardsticks of performance appraisal process which reduces and changes the traditional supervisor based appraisal method. This qualitative study has been carried out to discover whether 360 degree feedback is effective as the part of overall performance appraisal process highlighting results from previously conducted researches and also, made an attempt to deliver some recommendations about how to use it more efficiently. Results from the previous studies revealed that 360 degree feedback is an effective method for appraising employee performance despite of having a few drawbacks and can be more useful if integrated with some traditional methods.
Keywords: 360 Degree Feedback; Performance; Performance Appraisal; Employee; Firm, Evaluation; Employee Development